Penerapan Metode Taguchi Dalam Pengoptimalan Parameter Injection Moulding Terhadap Netto Produk Bioring Cone Cup - Ika Pramestiani; Bayu Wiro Karuniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Bioring Cone Cup products are produced by Sukodono molding industry with injection molding machine. However, at the beginning of production in getting the parameter value still uses a trial and error system, so this problem results in defects that cause the weight of the product is not in accordance with the agreement so that this product must be recycled again by spending a long time. With this problem, the company suffered losses because it had to pay compensation for production delays. Therefore, more study on the effect of optimizing injection molding settings on the net response of bioring cone cup products is required. This research uses the parameters of injection pressure, injection temperature, and cooling time. To identify the impact of various elements as well as the ideal manufacturing process parameters, the Taguchi technique is employed, with the rule that the smaller the signal to noise ratio, the better. From the experimental results, the optimal combination of variables is obtained, namely the injection pressure parameter at level 1 with a value of 80 bar, injection temperature at level 3 with a value of 230? , and cooling time at level 3 with a value of 0.5 seconds